Corporate Governance and Corporate Transparency of Indonesian Listed Companies - SAIFUL SAIFUL; PHUA LIAN KEE; HASNAH HARON (The Indonesian Journal of Accounting Research, 2013)
During Asian financial crisis in 1997, some Indonesian listed companies suffered by decreasing firm value and poor performance. The dominant factors that contributed to Asian financial crisis are poor corporate governance and a lack of transparency. As an attempt to improve corporate governance practice of Indonesian corporations, some reforms have been conducted by Indonesian regulatory authorities such as the code of good corporate governance with the objective to maximize shareholder and firm value by enhancing transparency, accountability, reliability, responsibility, and fairness. This study examined the relationship between those corporate governance attributes and corporate transparency of Indonesian listed companies by exploring the purposive sampling method, 88 companies were selected as the sample of this study. The finding of this study showed that board size and proportion of independent member on board positively affect corporate transparency. It means the corporate transparency will increase since the companies have large board and higher proportion of independent member on boards. In contrast, the proportion of board of directors who have family relationship is negatively associated with corporate transparency. It implies that family boards tend to advise management to disclose less information to public (less transparent) since they can get the informational benefit by transferring that information to their family. Meanwhile, the influence of family ownership, institutional ownership, management ownership, and foreign ownership on corporate transparency was not be supported by this study.